Valuation of properties in close proximity to waste dumps sites: The Nigeria experience - Bello, Victoria Amietsenwu; Bello, Mustapha Oyewole (International Journal of Strategic Property Management, 2009)
The paper identified and evaluated the techniques used by Nigerian Estate Surveyors and Valuers in valuing properties close to waste dump sites. A random sample of 107 Estate Surveyors and Valuers were taken from a sampling frame of 228 for the administration of questionnaire out of which 99 were returned. The data was analysed using the percentile, mean score and One Sample t‐test. The results show that majority of the Estate Surveyors and Valuers were not aware of the existence of methodologies used for the valuation of environmentally contaminated properties. The result further showed that the Estate Surveyors and Valuers over value properties in close proximity to the waste dump sites using inappropriate methods. In view of these findings, the undergraduate and post‐graduate curricula in Estate Management in the tertiary institutions should be reviewed to incorporate the appropriate methods of valuation in use for environmentally contaminated properties and the Continuous Professional Development (CPD) programme for the practitioners should be tailored to addresses this area of deficiency.First Publish Online: 18 Oct 2010